Development of prevalence and incidence of non-tuberculous mycobacteria in German laboratories from 2016 to 2020 - Caroline Corbett; Philipp Finger; Marion Heiß-Neumann; Juergen Bohnert; Ines B. Eder; Melanie Eisele; Inna Friesen; Achim J. Kaasch; Jan Kehrmann; Roland Lang; Jürgen Rödel; Susann Roessler; et al. (Emerging Microbes and Infections, 2023)
Numbers of non-tuberculous mycobacteria (NTM) pulmonary diseases (PD) have been repeatedly reported as increasing over the last decades, particularly in Europe. Sound epidemiological data are however missing for most European regions. This study calculated prevalence and incidence of NTM recovered from patients’ lungs in Germany, the largest Central European country, over a five-year period. It furthermore determined regional particularities of NTM species and results from susceptibility testing. 22 German NTM laboratories provided their mycobacteriological diagnostic data of 11,430 NTM isolates recovered from 5998 pulmonary patients representing 30% of all notified NTM-PD cases of Germany from 2016 to 2020. NTM incidence and prevalence were calculated for every study year. The presented epidemiological indicators are particularly reliant as TB surveillance data were used as a reference and TB notification reaches almost 100% in Germany. Laboratory incidence and prevalence of NTM recovered from respiratory samples ranged from 4.5–4.9 and from 5.3–5.8/100,000 for the population of Germany, respectively, and did not change over the five-year study period. Prevalence and incidence were stable also when stratifying for facultative pathogenic NTM, M. avium/intracellulare complex (MAIC), and M. abscessus/chelonae complex (MABSC). The proportion of NTM with drug susceptibility testing (DST) increased from 27.3% (2016) to 43.8% (2020). The unchanging laboratory NTM prevalence/incidence in Germany represents a “ceiling” of possible NTM-PD notification when diagnostic strategies do not change in the coming years. A notable increase in NTM-DST may indicate better notification of NTM-PD and/or awareness of new clinical guidelines but still remains below clinical needs.